Introduction to In Anticipation: Eschatology and Transcendence in Contemporary Contexts - Sands, Justin (Religions, 2017)
Although it is difficult to pinpoint when the so-called theological turn in Continental philosophy began in the 20th century, it is fair to consider as a working origin that Martin Heidegger's critique of metaphysics and his questioning of the forgetfulness of Being touched a nerve within both philosophical and theological discourses.[...]